Formação para a ciência: o uso de games para o desenvolvimento de competências entre os calouros cotistas de universidades públicas - Pinto, Wellington José Gonçalves (2023)
This project aims to develop a prototype game that maps previous competencies in order to manifest the strengths of quota freshmen in the area of exact and earth sciences in public universities for the brief university adjustment. Thus, some of the steps were to verify the design of games for the popularization of science; to observe the potential of this media for the development of young scientists; as well as, to infer means for the mapping of competencies for science. To this end, exploratory research was used as a method for the collection of secondary data, through the study of the theoretical reference on games and the prerequisite skills desirable for higher education in the 21st century. In addition, primary data resulting from focus groups with technicians, professors, students, and recent graduates of a federal university were added to the study. From the data analysis it was possible to perceive the potential of games both for scientific dissemination and for training cognitive skills of information processing, working and operational memory, problem solving, logical and mathematical reasoning, etc. The analysis also highlights Design Thinking as a suitable method for creative game modeling given its centrality to the lifestyle and issues of the strategic audience segment. Finally, through all the study carried out, it was possible to confirm that a game that assesses prior competencies and denotes certain gaps in knowledge, skills and attitudes, or competencies, to be developed or renewed, can assist in university adjustment, in effect, in training for science.